Effects of Different Light Spectra and Intensities on Stomatal Function in Lettuce and Basil - Salehinia Shafieh; Didaran Fardad; Aliniaeifard Sasan; Macpherson Sarah; Orsat Valérie; Lefsrud Mark (Journal of Horticultural Research)
Light quality and intensity markedly influence stomatal activity, a crucial physiological process regulating gas exchange and water loss in higher plants. Stomata dynamically open and close in response to environmental signals, facilitating carbon dioxide uptake for photosynthesis while modulating transpirational water loss. Although red and blue light are well-established regulators of stomatal function, the effect of green light on this process remains comparatively underexplored. In this study, the effects of multiple light wavelengths (430 nm, 530 nm, 560 nm, and 630 nm) and intensities (50, 75, 100, and 400 µmol·m−2·s−1) on stomatal responses in lettuce (Lactuca sativa) and basil (Ocimum basilicum) were systematically evaluated. The results showed that green light (530 nm and 560 nm) effectively maintained stomatal closure at lower intensities, thereby minimizing water loss and preserving tissue freshness during postharvest storage. These findings highlight the potential application of green light to optimize postharvest handling by reducing transpiration and improving shelf life of leafy crops. This evidence provides a foundation for targeted light management strategies aimed at improving the commercial quality and marketability of horticultural produce.